EFL students’ perceptions of interactive slides (Pear Deck) in blended and online flipped classrooms - Kiki Juli Anggoro; Damar Isti Pratiwi (Social Sciences and Humanities Open)
This study examines university students’ perceptions of interactive slides, specifically Pear Deck, in two flipped English as a Foreign Language (EFL) classroom environments: blended and online flipped classrooms. A total of 490 students from a public university in Thailand participated, with 258 enrolled in online English lessons and 232 in face-to-face courses. Participants were selected from existing courses taught by the same lecturer. Using a sequential explanatory design, the study integrates quantitative survey data and qualitative feedback to assess the effectiveness of interactive slides in enhancing student engagement, learning experiences, and English skill development. Findings indicate that both flipped environments elicited positive perceptions, with traditional classrooms showing slightly higher satisfaction (M = 4.63) than fully online classrooms (M = 4.35). Inferential statistics revealed significant differences between the two groups across survey categories (p < .05), with traditional classrooms scoring higher on engagement, learning experiences, and English skills development. Qualitative feedback highlighted technical challenges in online settings, language anxiety in traditional classrooms, and suggestions for improving workload balance and activity diversity. This study provides valuable insights into the role of interactive slides in flipped learning environments and offers practical guidance for EFL educators seeking to enhance engagement and learning outcomes through technology integration.